If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 6r + 1 Reorder the terms: 25 = 1 + 6r Solving 25 = 1 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 25 + -6r = 1 + 6r + -6r Combine like terms: 6r + -6r = 0 25 + -6r = 1 + 0 25 + -6r = 1 Add '-25' to each side of the equation. 25 + -25 + -6r = 1 + -25 Combine like terms: 25 + -25 = 0 0 + -6r = 1 + -25 -6r = 1 + -25 Combine like terms: 1 + -25 = -24 -6r = -24 Divide each side by '-6'. r = 4 Simplifying r = 4
| 4y^3-7y^2-16y+28= | | 35.9x+7.19y=31.595 | | -55x-65=71+6x | | -14=7(-3+n) | | -8(3+n)=32 | | -56=-7(p-7) | | -63x+89=22-63x | | -16=3+n | | 9x^2+3=147 | | 7x^2-105-0=0 | | -2=2v+6 | | -31=-7+4u | | 1.20*400= | | -8+3y=-23 | | 2(x+12)=0 | | (2x-17)=(3x+10) | | -24=4(1+x) | | 26=3w-10 | | 2s-6=4 | | 9w/3 | | 2w+13=29 | | X^2+2x+y^2-10=0 | | 49=4v+9 | | -1=x/15 | | 3u-8=40 | | 5d+3=18 | | 5x+3=-x-21 | | 5n-1+5n-3=26 | | h=372/(3x*x) | | 2x+5+c=0 | | x-x^2-2x=0 | | 14x-5+5-12x= |